Biochemical Characterization of a First Fungal Esterase from Rhizomucor miehei Showing High Efficiency of Ester Synthesis - Liu, Yu; Xu, Haibo; Yan, Qiaojuan; Yang, Shaoqing; Duan, Xiaojie; Jiang, Zhengqiang (PLOS ONE, 2013)
Background Esterases with excellent merits suitable for commercial use in ester production field are still insufficient. The aim of this research is to advance our understanding by seeking for more unusual esterases and revealing their characterizations for ester synthesis. Methodology/Principal Findings A novel esterase-encoding gene from Rhizomucor miehei (RmEstA) was cloned and expressed in Escherichia coli. Sequence analysis revealed a 975-bp ORF encoding a 324-amino-acid polypeptide belonging to the hormone-sensitive lipase (HSL) family IV and showing highest similarity (44%) to the Paenibacillus mucilaginosus esterase/lipase. Recombinant RmEstA was purified to homogeneity: it was 34 kDa by SDS-PAGE and showed optimal pH and temperature of 6.5 and 45°C, respectively. The enzyme was stable to 50°C, under a broad pH range (5.0–10.6). RmEstA exhibited broad substrate specificity toward p-nitrophenol esters and short-acyl-chain triglycerols, with highest activities (1,480 U mg−1 and 228 U mg−1) for p-nitrophenyl hexanoate and tributyrin, respectively. RmEstA efficiently synthesized butyl butyrate (92% conversion yield) when immobilized on AOT-based organogel. Conclusion RmEstA has great potential for industrial applications. RmEstA is the first reported esterase from Rhizomucor miehei.